Persistent Inflammatory Activity in Blood Cells and Artery Tissue from Patients with Previous Bare Metal Stent - Farsky,Pedro Silvio (2018)
Abstract Background: Studies have pointed out a higher mortality after coronary artery bypass surgery (CABG) in patients with stent. Objective: To evaluate inflammatory markers in peripheral blood cells and in coronary artery tissue samples obtained during CABG in patients with stent compared to controls. Methods: The case series consisted of two groups, one with previous stent implantation (n = 41) and one control (n = 26). The expression of the LIGHT, IL-6, ICAM, VCAM, CD40, NFKB, TNF, IFNG genes was analyzed in peripheral blood cells collected preoperatively. The coronary artery was evaluated for: interleukin-6, ICAM, VCAM, CD40, NFKB, TNF-alpha and IFN-gamma by immunohistochemistry. A total of 176 tissue samples were grouped for analysis in: A1- arteries with stent (n = 38); A2- native arteries from patients with stent in another artery (n = 68); and A3- arteries without stent from controls undergoing routinely CABG surgery (n = 70). A significance level of 0.05 was adopted. Results: Patients with stent showed higher TNF (p = 0.03) and lower CD40 gene expression (p = 0.01) in peripheral blood cells than controls without stent. In coronary artery samples, the TNF-alpha protein staining was higher in the group A1, not only in the intima-media layer (5.16 ± 5.05 vs 1.90 ± 2.27; p = 0.02), but also in the adipose tissue (6.69 ± 3.87 vs 2.27 ± 4.00; p < 0.001). Furthermore, group A1 had a higher interleukin-6 protein staining in adipose tissue than group A3 (p = 0.04). Conclusion: We observed a persistently higher systemic TNF expression associated with exacerbated TNF-alpha and interleukin-6 local production in patients with stents. This finding may contribute to a worse clinical outcome.